Terminologies that characterize the visual and physical properties of wood carving as cultural heritage - Kamaruddin, Zumahiran; Zakariya, Khalilah; Nazuki, Siti Najwa (American Scientific publishers, 2017)
This study aims to investigate the physical and visual properties of the traditional Malay wood carving as cultural heritage component, which has been inherited from the old generation of carvers since 16th century. The objectives of this study are: 1) to identify the tangible and intangible attributes of the wood carving components that denote its cultural heritage value, and 2) to analyse the characteristics and physical properties of the wood components. Personal interview with Malay carvers, field observation, visual and laboratory analyses were conducted to determine the physical and chemical properties of the selected wood carving components from Terengganu and Kelantan. The result of analyses characterized the traditional concepts of carving into transfiguration, transformation, translation, transference, transcendence, transmission, translocation, and transition. Also, the result of laboratory test shows that different types of wood especially Meranti and Cengal were used for the fabrication of carving components. The study found that Cengal-based wood carving has distinctive physical and chemical characteristics thus distinguished it from those found in Meranti-based wood carving. The study suggests the visual and physical characteristics of the carving components characterize their heritage values. These characteristics determine the distinctiveness of the carved components that has become the key determinants to their heritage attributes resulting to significant pieces of work. Future research could be conducted to determine the suitable method for preserving the wood carving as cultural heritage. The Malay traditional wood carving need to be protected to ensure its cultural heritage values are maintained in good condition.